DOI: 10.26512/2016.04.d.20792
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a migração transuterina e a razão sexual de conceptos em bovinos da raça Nelore (Bos taurus indicus)

Abstract: Capítulo I 1 1-Introdução 1 2-Revisão de Literatura 3 2.1-Gestação em bovinos e particularidades para Bos taurus indicus 3 2.2-Frequência gestacional em cornos uterinos direito e esquerdo 5 2.3-Migração transuterina de embriões bovinos 7 2.4-Razão e predileção sexuais nos cornos uterinos 2.5-Fetometria de conceptos bovinos 3-Referências Bibliográficas Capítulo II 1-Resumo 2-Abstract 3-Introdução 4-Materiais e Métodos 4.1-Animais 4.2-Levantamento de dados das gestações 4.2.1-Corno uterino gestante e corpo lúteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
0
0
Order By: Relevance
“…Ht, MCV, and TPC values showed no difference between groups, and their results are similar to those obtained by [37] in Nellore and Holstein breeds, [48] in Norwegian Red, [49] in Pantaneira, and [9] in Hanwoo; while the variables Hb and CHC showed values compatible with similar studies in other races and different age groups [50][51][52]. Age did not influence the behavior of the erythrometric variables between the groups, corroborating the results of [40,49,53,54].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Ht, MCV, and TPC values showed no difference between groups, and their results are similar to those obtained by [37] in Nellore and Holstein breeds, [48] in Norwegian Red, [49] in Pantaneira, and [9] in Hanwoo; while the variables Hb and CHC showed values compatible with similar studies in other races and different age groups [50][51][52]. Age did not influence the behavior of the erythrometric variables between the groups, corroborating the results of [40,49,53,54].…”
Section: Discussionsupporting
confidence: 89%
“…Lymphocytes are the dominant cell type in the bovine species, and their count varies with age [68]. The mean values observed for the leukocyte variables are similar to those obtained by [37] in Nellore and Holstein breeds and by [49,69] in the Pantaneira breed, all in the same age group, but with an increase, because it is known that in this age group there is a predominance of lymphocytes [37,49]. Such variation can be credited to the high environmental temperature, which corroborates with [70], who observed that there is higher leukocyte activation in Holstein neonates at different environmental temperatures.…”
Section: Discussionsupporting
confidence: 85%
“…The level of GGT and ALP decline in adult sheep, which were consistent with the findings of Borges et al (2011), andSanto Da Cruz et al (2017), who revealed higher level in younger compared to adult sheep; however, in the study of Daramola et al (2005), ALP lev- Mean values within the same row with different superscripts differ at P<0.05.…”
Section: Age and Liver Parameterssupporting
confidence: 88%